2014
DOI: 10.1016/j.scijus.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the use of vacuum metal deposition versus cyanoacrylate fuming for visualisation of fingermarks and grab impressions on fabrics

Abstract: Both vacuum metal deposition (VMD) and cyanoacrylate fuming (CAF) are techniques used to visualise latent fingermarks on smooth non-porous surfaces such as plastic and glass. VMD was initially investigated in the 1970s as to its effectiveness for visualising prints on fabrics, but was abandoned when radioactive sulphur dioxide was found to be more effective. However, interest in VMD was resurrected in the 1990s when CAF was also used routinely. We now report on studies to determine whether VMD or CAF is the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
3
11
0
1
Order By: Relevance
“…These studies applied traditional gold/zinc [12] and silver [13] on dark fabrics to varying degrees of success. Further studies on fabric compared VMD and superglue fuming, which proved VMD to be more effective at developing fingermarks [14]. Despite the recent resurgence in VMD work and the price of VMD chambers dropping substantially over the last decade, very little has emerged recently comparing the efficiency of VMD in developing latent fingermarks on polymer banknotes, and other polymer substrates in general [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These studies applied traditional gold/zinc [12] and silver [13] on dark fabrics to varying degrees of success. Further studies on fabric compared VMD and superglue fuming, which proved VMD to be more effective at developing fingermarks [14]. Despite the recent resurgence in VMD work and the price of VMD chambers dropping substantially over the last decade, very little has emerged recently comparing the efficiency of VMD in developing latent fingermarks on polymer banknotes, and other polymer substrates in general [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It would be expected that as time passed marks would become less detailed and, hence, less visible, as was observed by Fraser et al in two separate studies [20,30]. Nevertheless, the authors did concede that, on occasion, the trend deviated and more detail was visualised on older samples [20].…”
Section: (A) Empty Grab Marks (Day 14 Donor 1 Black Polyester) (B)mentioning
confidence: 79%
“…As most studies involving Lumicyano have been conducted on non-or semi-porous substrates, there was an interest to perform several studies on porous materials such as fabrics. In 2013, Fraser et al [30] compared the visualisation of fingermarks on fabrics using vacuum metal deposition (VMD) to cyanoacrylate fuming (CAF). VMD visualised marks better than the CAF method, which is the opposite of what had been previously discovered with non-and semi-porous substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Fraser et al (2014) suggested the use of vaccum metal deposition (gold and zinc) over cyanoacrylate fuming method for developing latent fingermarks on different kinds of fabrics such as nylon, polyester, cotton and polycotton as it produced greater ridge detail and more effective than latter one. Dominick and Laing (2011) suggested the use of cyanoacrylate fuming followed by gun blue followed by brilliant yellow 40 dye staining and cyanoacrylate fuming followed by palladium deposition over cyanoacrylate fuming followed by brilliant yellow 40 dye staining, cyanoacrylate fuming followed by gun blue, powder suspension and palladium suspension for developing latent fingermarks on unfired brass cartridge cases.…”
Section: Evaluation Of Cyanoacrylate Fuming Methodsmentioning
confidence: 99%